Evaluation of Serum Aspergillus‐Specific Immunoglobulin A by Indirect ELISA for Diagnosis of Feline Upper Respiratory Tract Aspergillosis. (1st September 2016) - Taylor, A.; Peters, I.; Dhand, N.K.; Whitney, J.; Johnson, L.R.; Beatty, J.A.; Barrs, V.R.
Abstract : Background: Serological tests for diagnosis of aspergillosis in immunocompetent humans and animals are based on Aspergillus ‐specific IgG (As‐IgG). In humans with chronic pulmonary aspergillosis, As‐IgA may be detectable even if IgG titers are negative. Cats with upper respiratory tract aspergillosis (URTA) have detectable As‐IgG, but their ability to mount an IgA response and its diagnostic utility are unknown. Objectives: To determine whether serum As ‐ IgA can be detected in cats with URTA and evaluate its diagnostic utility alone or combined with As ‐ IgG. Animals: Twenty‐three cats with URTA (Group 1), 32 cats with other respiratory diseases (Group 2), and 84 nonrespiratory controls (Group 3). Methods: Serum As‐IgA and As‐IgG was measured by indirect ELISA. Optimal cutoff values were determined by receiver‐operating curve analysis. Sensitivity (Se) and specificity (Sp) for URTA diagnosis were determined. Results: Serum IgA was detected in 91.3% of Group 1 cats. The Se of IgA detection was 78.3% and Sp was 96.9% for Group 2, 85.7% for Group 3 and 88.8% for Group 2 and 3 combined. Assay Se for IgG was 100% and Sp was 92.2%. Using combined IgA and IgG results at cutoffs optimized for Sp for IgA and Se for IgG and combined controls (Groups 2 and 3), Se for diagnosis was 100% and Sp was 91.4%. Conclusion and Clinical Importance: Most cats with URTA have serum As‐IgA antibodies that can be detected by ELISA. Paired measurement of serum As‐IgA and IgG shows no benefit for diagnosis of feline URTA over IgG alone.